Teaching Strategies for Enhancing Future Thinking Skills in Secondary Education: A Systematic Literature Review - Suhendar, Suhendar; Widodo*, Ari; Solihat, Rini; Riandi, Riandi; Chaw, Ei Phyu (Jurnal IPA & Pembelajaran IPA, 2025)
The rapid changes in science, technology, and global challenges require students to develop future thinking skills to anticipate and adapt to uncertainties. However, many secondary education curricula do not explicitly emphasize these skills, leading to a gap in students' ability to plan, predict, and engage in future-oriented decision-making. This study aims to review the literature on effective strategies in improving future thinking skills in secondary education. The research method used is systematic literature review which involves the analysis of various studies from the scopus and web of science databases. The research sample consisted of 213 articles that were filtered to 28 relevant articles. Data analysis was carried out by identifying and categorizing teaching strategies found in the literature and evaluating the effectiveness, obstacles, and role of teachers and the curriculum in their implementation. The findings of the study show that strategies such as future episodic thinking, the use of information and communication technology, and positive foresight are effective in developing students' future thinking skills. The main obstacles identified included limited technological resources, lack of understanding and support from teachers and school administration, and cultural and social challenges. The discussion suggests that the integration of future thinking skills in the curriculum, the use of interdisciplinary approaches, and adequate teacher training can overcome these barriers. This research provides recommendations to improve the implementation of teaching strategies that can prepare students for a future full of challenges and uncertainties